Immune checkpoint inhibitors efficacy across solid cancers and the utility of PD-L1 as a biomarker of response: a systematic review and meta-analysis - Fitzsimmons, Timothy S.; Singh, Niharika; Walker, Thomas D. J.; Newton, Claire; Evans, Dafydd G. R.; Crosbie, Emma J.; Ryan, Neil A. J. (Frontiers in Medicine, 2023)
Background: Immune checkpoint inhibitors (ICPI) are a tumour agnostic treatment. However, trials of their use have been site specific. Here we summarise the trial data and explore the utility of programmed death-ligand 1 (PD-L1) expression as a biomarker to direct their pan-cancer use. Method: Databases were searched from conception to May 2022 limited to the English language. The search terms and method were devised by a specialist medical librarian. Studies were limited to adults with solid cancers (excluding melanomas) treated with ICPIs. Only phase III randomised control trials (RCT) were included. Where present in eligible clinical trials, hazard ratios (HR), risk ratios (RR), standard error (SE) and 95% confidence intervals (CI) were extracted or calculated. Heterogeneity across studies was described with the use of an I2 score. Results: In total 46,510 participants were included in the meta-analysis. Overall, meta-analysis favoured the use of ICPIs with an overall survival (OS) HR of 0.74 (95% CI 0.71 to 0.78. Subgroup analysis comparing studies in which most cancers demonstrated PD-L1 expression vs those studies in which a minority of cancer demonstrated PD-L1 expression reported similar effect of ICIP use on OS. Specifically, studies with minority PD-L1 expression had an HR 0.73 (95% CI 0.68 to 0.78) vs studies with majority PD-L1 expression HR 0.76 (95% CI 0.70 to 0.84). Finally, the use of ICPIs led to an improved side effect profile when compared with standard chemotherapy (RR 0.85 (95% CI 0.73 to 0.98)). Conclusion: ICPIs improve survival outcomes in cancer types. These effects are seen in the primary, recurrent, chemotherapy sensitive, chemotherapy resistant disease. However, PD-L1 as a biomarker for the targeting of ICPI use seems problematic. Other biomarkers such as mismatch repair or tumour mutational burden should be explored in randomised trials.